Covid-19 impact on Zimbabwean agricultural supply chains and markets: a sustainable livelihoods perspective - Rukasha, Tanyaradzwa; Nyagadza, Brighton; Pashapa, Rumbidzai; Muposhi, Asphat (Cogent OA, 2022)
The purpose of the article is to analyse the impact of COVID-19 on the agricultural supply chains and markets in Zimbabwe and subsequent effect on livelihoods. The research methodology that was applied is a systematic literature survey anchored on inductive research approach. This article is based on the systematic review of secondary data sources, such as journals, policy reports, as well as reports from national and international organizations. The review involved a predetermined and comprehensive approach of searching, analyzing and synthesizing extant literature on agricultural supply chains. In general, the pandemic has affected the whole supply chain from the food production systems and input supply, the storage and distribution, processing and packaging as well as the retail and marketing aspect. The research showed that the COVID-19 pandemic severely threatens an already critical food security situation arising mainly from the prevailing poor macroeconomic conditions and consecutive years of drought in Zimbabwe. This has led to a higher than previously anticipated food insecure population, especially in urban centers. Over 70% of the workers are self-employed and a vast majority operate in the informal sector. The informally employed represent a significant breadwinner constituency, whose dependents comprise vulnerable sections of the populace. The restrictions on mobility and the closure of borders meant immediate loss of employment and income. The study revisited the previous viruses such as Ebola to extrapolate though marginally, the implications of the COVID-19 pandemic. Using secondary sources and the general agriculture supply chain to guide understanding, the findings show that unless measures are put in place to safeguard farmers especially smallholder activities in Zimbabwe, COVID-19 has the potential to reproduce the same catastrophic implications created by Ebola in West Africa countries where peasant food systems where shattered and livelihoods strategies maimed.